2007
DOI: 10.1080/03079450701338755
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of environmental salmonella contamination in caged and free-range layer flocks

Abstract: The environmental contamination by salmonella was examined over a 12-month period in 74 commercial layer flocks from eight farms in the UK, which previously had been identified as being contaminated with salmonella. Samples of faeces, dust, litter, egg belt spillage and wildlife vectors were taken, plus swabs of cages, feeders, drinkers, floors, egg belts and boots. Some sampling was performed in each month of the year. Numerous serovars were detected but Salmonella enterica serotype Enteritidis was the only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 40 publications
6
71
2
2
Order By: Relevance
“…This finding contrasts with an earlier study that found increasing Salmonella shedding over the sampling period (13). There was no significant effect of season on Salmonella prevalence during this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding contrasts with an earlier study that found increasing Salmonella shedding over the sampling period (13). There was no significant effect of season on Salmonella prevalence during this study.…”
Section: Discussioncontrasting
confidence: 99%
“…During our study, variabilities between the detected prevalence and shedding were observed between flocks and farms. This observation is in agreement with previous reports (13,16). There are numerous reports on the effects of the housing system on the shedding of Salmonella spp.…”
Section: Discussionsupporting
confidence: 94%
“…According to a longitudinal study of environmental Salmonella contamination in caged and free-range layer flocks carried out by Wales et al (2007), the timing of taking samples has been shown to have a significant influence on Salmonella spp. isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Cleaning and disinfection in cases when organic matter had been substantially removed and disinfectants were adequately applied and in proper concentration, had a positive influence on Salmonella control. However, the wildlife reservoirs, multiage farming and lack of "all in all out" strategy highlight the need for vaccination and the use of probiotics in flocks with high and low incidence of the pathogen's load or even in cases that it is absent (Wales et al, 2007). Another study by Dewaele et al (2012) which aimed to examine the Salmonella enterica serovar Enteritidis environmental contamination on persistently positive layer farms in Belgium during successive laying cycles showed that in contaminated poultry houses, neither vaccination nor cleaning and disinfection are considered as the only prerequisite for successful elimination of Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an increased tendency for flocks to be identified as Salmonella positive as the birds become older (Garber et al, 2003;van de Giessen et al, 2006;Wales et al, 2007;Bouzidi et al, 2012;Roberts et al, 2013) especially if birds have been moulted (Golden et al, 2008) In most cases, the initial infection resulted from residual contamination of laying houses that spread to pullets that are suffering from transport, handling and relocation/remixing stress at a time when hormonal changes associated with the onset of lay are also increasing susceptibility to infection (Line et al, 1997). This leads to a typical early peak of infection within three weeks of housing (Humbert et al, 1995;Gradel et al, 2002) but laying flocks are rarely sampled at this time (16-19 weeks of age).…”
Section: Factors Influencing Detection Of Salmonella Infected Flocksmentioning
confidence: 99%